Faktor yang Mempengaruhi Turnover Intention Karyawan (Studi Kasus : PT. BANK SYARIAH INDONESIA, Tbk KC MAKASSAR 2) - Munawir Nasir; Muh. Haerdiansyah Syahnur; Mutmainnah Hasan (FEB Universitas Sam Ratulangi Manado, 2022)
The purpose of this study is to ascertain the effect of Organizational Citizenship Behavior (OCB) on the Turnover Intentions of employees at PT. Bank Syariah Indonesia Tbk KC Makassar 2 and the effect of Job Satisfaction on the Turnover Intentions of employees at PT. Bank Syariah Indonesia Tbk KC Makassar 2. Â The descriptive statistical test analysis method and the statistical inferential test were used in this study. The sample consisted of employees of PT. Bank Syariah Indonesia Tbk Kc Makassar 2. Organizational Citizenship Behavior (OCB), Job Satisfaction, and Turnover intention are the variables examined. Organizational Citizenship Behavior (OCB) was found to have a negative and significant effect on Turnover Intention at PT. Bank Syariah Indonesia Tbk KC Makassar 2. Existence of voluntary behavior to assist others in their work results in a decrease in Turnover Intention at PT. Bank Syariah Indonesia Tbk KC Makassar 2. And at PT. Bank Syariah Indonesia Tbk KC Makassar, Job Satisfaction has a negative and significant effect on Turnover Intention. Employee satisfaction with their jobs correlates with a lower level of Turnover Intention at PT. Bank Syariah Indonesia Tbk KC Makassar 2.